The Extraterritorial Regulation of Clearinghouses. Issue 1 (12th March 2016) - Yadav, Yesha; Turing, Dermot
Abstract: This article argues that post-Crisis reform of over-the-counter derivatives is in trouble. While regulators agree on the broad strokes of regulation, they diverge on the detail, often on core issues like how clearinghouses should manage risk. In examining divergences between the USA and Europe, this article makes three points. First, divergences in clearinghouse regulation matter in derivatives markets because these markets are uniquely international in scope. Contracts involve counterparties in different countries. Many transactions comprise cross-border aspects lacking a geographical anchor. Where derivatives traders face legal uncertainty, they can be dis-incentivized from observing laws or motivated to seek out the lowest cost compliance options. Secondly, although the USA and European Union (EU) have adopted common ground rules, their approaches to implementation differ in matters of detail. Such divergences prevent regulators from recognizing each other's clearinghouses as sufficiently robust. Thirdly, while acknowledging that mutual recognition is the most appropriate way forward, substantial shortcomings exist with this approach. This article highlights continuing areas of structural divergence—like access to emergency funding and bailouts—that impact the costs of the EU and US regimes. Where costs diverge, traders will seek out avenues for regulatory arbitrage to lower costs of compliance. In concluding, this article explores implications for reform.